Muscle disorders: the latest investigations. Issue 9 (4th September 2013) - Ghaoui, R.; Clarke, N.; Hollingworth, P.; Needham, M.
Abstract: Patients with muscle disorders can present a diagnostic challenge to physicians because of the different ways they can present and the large number of different underlying causes. Recognition of the 'myopathic phenotype' coupled with investigations usually including electrodiagnostic and histological investigations have been essential for diagnosing the underlying cause of a myopathy. Despite these standard investigations, some patients can remain undiagnosed. New tests including more specific antibody tests for immune‐mediated myopathies and the introduction of next‐generation sequencing promise to revolutionise diagnostic approaches for immune and inherited myopathies, but clinical expertise remains essential to choose the most appropriate tests and interpret the results. The aim of this review is to provide an overview of the different presentations to the neuromuscular clinic and the latest investigations that can be helpful in the diagnosis of muscle disorders.